Girls and Boys Have a Different Cardiometabolic Response to Obesity Treatment - Dalla Valle, Marketta; Laatikainen, Tiina; Potinkara, Hanna; Nykänen, Päivi; Jääskeläinen, Jarmo (Frontiers in Endocrinology, 2018)
Background: Childhood obesity exposes individuals to cardiometabolic disturbances. We analyzed how family-based multidisciplinary obesity treatment influenced children’s cardiometabolic health. Materials and methods: In this retrospective, two-year, follow-up study of 654 2- to 18-year-old children treated for obesity in three Finnish pediatric clinics in 2005-2012, blood pressure (BP), metabolic parameters, and the influence of a change in body mass index standard deviation score (BMI SDS) were analyzed. Results: At baseline, at least one cardiovascular risk factor was present in 474 (80%) cases. Girls had no significant changes in cardiometabolic parameters during the treatment. Boys’ total cholesterol (TC) improved by 12 months (P = 0.009), and their low-density lipoprotein C (LDL-C) and glycosylated hemoglobin ameliorated by 12 months (P = 0.030 and 0.022, respectively) and 24 months (P = 0.043 and 0.025, respectively). Boys’ triglycerides, insulin, homeostasis model assessment for insulin resistance (HOMA-IR) and systolic BP deteriorated at 24 months (P < 0.001, 0.004, 0.002, and 0.037, respectively). If BMI SDS reduced > 0.25 by 12 months, the number of acceptable TC, LDL-C, insulin, and HOMA-IR values increased. Conclusion: The girls’ obesity treatment outcomes comprised no cardiometabolic improvements, and most outcomes of the boys were unfavorable. These findings indicate the need to assess treatment methods and focus on prevention.